2022
DOI: 10.1097/olq.0000000000001725
|View full text |Cite
|
Sign up to set email alerts
|

High Cure Rate Among Pregnant Women in a Chlamydia trachomatis and Neisseria gonorrhoeae Testing and Treatment Intervention Study in Gaborone, Botswana

Abstract: Between March 2021 and March 2022, 251 pregnant women were tested for Chlamydia trachomatis and Neisseria gonorrhoeae infection in Botswana. Fifty-eight (23%) tested positive for at least 1 infection, and 57 (98%) were treated. No participants tested positive at test of cure. In some settings, cost of test of cure may outweigh the benefits.C hlamydia trachomatis and Neisseria gonorrhoeae are curable sexually transmitted infections (STIs) that are linked to adverse pregnancy and neonatal outcomes, including pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Other studies have demonstrated that azole resistance is an important cause of VVC treatment failure 27,28 . Finally, a repeat STI within 1 month from the same or a new sex partner may occur, but this likely only contributes to a small proportion of cases 29,30 . We did not observe an association between a new sexual partner and treatment failure, and only 1 incident of STI was detected among the small group of women with microbiological evaluation of their treatment failure.…”
Section: Discussioncontrasting
confidence: 67%
“…Other studies have demonstrated that azole resistance is an important cause of VVC treatment failure 27,28 . Finally, a repeat STI within 1 month from the same or a new sex partner may occur, but this likely only contributes to a small proportion of cases 29,30 . We did not observe an association between a new sexual partner and treatment failure, and only 1 incident of STI was detected among the small group of women with microbiological evaluation of their treatment failure.…”
Section: Discussioncontrasting
confidence: 67%
“…The single untreated participant tested positive again at PNC. Further detailed findings from the Maduo Study have been reported elsewhere 23,24 …”
Section: Resultsmentioning
confidence: 87%
“…Further detailed findings from the Maduo Study have been reported elsewhere. 23,24 Participants testing positive at any time point were included in this analysis (n = 89; Table 1). Across all time points, there were 95 total positive test results.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment was provided on the same day of results according to the United States Centers for Disease Control and Prevention (CDC) guidelines. 17 Mothers were treated with oral azithromycin 1 G for C. trachomatis , and 500 mg intramuscular ceftriaxone injection for N. gonorrhoeae . Infants were treated with oral erythromycin (liquid formulation) 50 mg/kg/day for 14 days in four divided doses per day for C. trachomatis , and intramuscular ceftriaxone single-dose 25–50 mg/kg for N. gonorrhoeae .…”
Section: Methodsmentioning
confidence: 99%
“…34 The few published antenatal STI prevalence studies suggest a baseline antenatal C. trachomatis prevalence ranging from 8% 16,35 to 23%. 17,36 There are no published epidemiological estimates for ophthalmia neonatorum.…”
Section: Evidence Reviewmentioning
confidence: 99%